Speaking in Tongues: Commentary on Cubero, de la Mata and Cubero - Zittoun, Tania (My University, 2008)
Cubero, de la Mata and Cubero show that women who have attended some formal adult education are able to solve a task in a manner that suggests that they master conceptual thinking more than do women just starting such education. I suggest that this interpretation is based on models of learning that do not fully take into account the person actively engaged in making sense of the situation. Focusing on three theoretical issues—the language—thinking relationship, adult learning, and the transfer of knowledge in the test situation—I propose to reinstall an active person, and I consequently propose an alternative interpretation of the data.
Keywords: adult learning; settings; task solving